THE INFLUENCE OF DIGITAL SKILLS, WORK DISCIPLINE AND WORK MOTIVATION ON THE PERFORMANCE OF TEACHERS AT SMK NEGERI 1 LHOKSUKON - Surainalia; Yanita; Marbawi; Sullaida (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the influence of each variable that is interrelated between each other on employee performance, namely team work, innovative behavior, and work environment at the Idi Timur Health Center, East Aceh Regency. The free variables in this study are team work, innovative behavior and work environment, while the bound variables are employee performance. The type of research uses a questionnaire that contains statements by distributing them to the employees concerned at the Idi Timur Health Center, East Aceh Regency. East Idi Health Center, East Aceh Regency. The scoring technique uses a Likert scale. Where with a population of 61 employees and will be used as a sample of 61 respondents. This study uses the Multiple Linear Regression Analysis model with the SPSS (Statistical Program For Social Scince) program. The results of this study are that team work, innovative behavior, and work environment have a positive and significant effect on employee performance at the East Idi Health Center, East Aceh Regency. The better the teamwork , the better the employee performance, as well as the increase in innovative behavior and work environment, the better the employee performance produced.